Hendrickson Reagent Induced Rearrangement of Aryl Propargyl Alcohols To α,β-Unsaturated Aldehydes - Moussa, Ziad; Aljuhani, Ateyatallah (Letters in Organic Chemistry, 2018)
The Hendrickson reagent (triphenylphosphonium anhydride trifluoromethanesulfonate), prepared from the reaction of triphenylphosphine oxide (Ph3PO) and triflic anhydride (Tf2O) (2:1 stoichiometry), promotes dehydrations and various coupling reactions. The reagent has been used to transform oximes to nitriles and to prepare esters, amides and many other functional groups through the intermediacy of an alkoxyphosphonium salt. The reagent proved useful in heterocycle synthesis of thiazolines, imidazolines, quinoline precursors, isoquinolines, β-carbolines, phenanthridines, 11Hindolo[ 3,2-c]quinolines, quinoline-lactones, furoquinolinones, and indolizino[1,2-b]quinolin-9(11H)- ones. Moreover, the reagent has been key to the successful total synthesis of several natural products. Aryl propargyl alcohols with a terminal α-acetylenic group undergo rapid conversion to the corresponding α,β-unsaturated aldehydes at room temperature in dichloromethane in the presence of one equivalent of triphenylphosphonium anhydride trifluoromethanesulfonate. The reaction involved adding freshly distilled Tf2O (1.0 mmol) to a solution of Ph3PO (2.0 mmol) in CH2Cl2 (10 mL) at 0 oC under N2 atmosphere. After stirring for 10 min, the propargyl alcohol (1.0 mmol) was added as a CH2Cl2 solution (2 mL), followed by the addition of water and Et3N (2.0 mmol) and further stirring at room temperature for 1h. Subsequent workup with 5% NaHCO3 (20 mL) and purification afforded α,β- unsaturated aldehydes. Eighteen aryl propargyl alcohol substrates with a terminal α-acetylenic group were transformed in good to excellent yields (71-85%) to enals. The methodology proved successful with secondary and tertiary alcohols with stereoselectivity favouring exclusively the E isomer. All the synthesized compounds are known and were characterized (1H, 13C, and M.P) and compared to literature values. The method offers several advantages such as exclusive stereoselectivity, short reaction time, good yield, mild reaction conditions, and simple operational procedure.
Keywords: α